Farmacoterapia potencialmente inapropriada para o idoso à luz da literatura científica - Santos, Ana Patrícia Alves Lima (2014)
INTRODUCTION. The greater predisposition to chronic diseases and consequent use of various medications in the elderly increases the chances of the use of potential inappropriate drug therapy (PIDT). The damaging effects of PIDT boosted professionals to develop methods to identify patterns of prescription PIDT in different countries and practice scenarios. PURPOSE Assess FPII the light of the scientific literature. METHODOLOGY. The study was structured in three stages. The first corresponded to a systematic review to identify what are the assessment tools used by the world FPII and investigate what are the terms used to refer to FPII. The second stage corresponded to a systematic review aimed to assess the methodological rigor of studies evaluating FPII. The third step corresponds to a meta-analysis that evaluated the association FPII with risk factors, age, sex and polypharmacy. RESULTS. The instrument most commonly used in the literature is the one proposed by Beers. Found more than 50 terms to refer to PIDT. Of the studies reviewed, none fulfilled all items proposed by the Strengthening the Reporting of Observational Studies in Epidemiology. Only polypharmacy had a positive association with the use of FPII. CONCLUSION. These findings should guide future research in this area, offering a more complete approach on aspects related to the use of medications for this specific population.